Gendered Geographies of the European East in the American Cold-War Literary Imaginary - Martyna Bryla (European Journal of American Studies)
In the American Cold-War imaginary, the representation of Eastern Europe was strongly influenced by male intellectuals and writers from the region, whose works were celebrated in the US not only for their artistic merits but most of all for their political import. As prominent émigrés like Czesław Miłosz explained the region to the Western intellectual public, native-born authors like Philip Roth contributed to shaping the Eastern European literary canon in the US by promoting Kafka, Konwicki, Kundera and other undeniably great if predominantly male authors. In this essay, I take a closer look at the imaginative geographies of the European East in the texts by John Updike, Philip Roth, Joyce Carol Oates, Patricia Hampl, and Eva Hoffman. I argue that while these imaginative geographies are indeed typified by a male figure, which frequently oscillates between the opposite poles of dissidence and conformism, the female figures should not be overlooked. The portrayal of women in the texts under study uncovers (and at times challenges) the fantasies, fears and concerns driving the East-West encounters which these texts dramatize, while at the same time providing interesting insights into gender and social dynamics behind and beyond the Iron Curtain.